Protocol for preparing youths leaving child and youth care centres in South Africa: Insights from social workers - Mbangula, Fezeka; Simeon De Jager, Elzahne (Social Work/Maatskaplike Werk, 2025)
There is still limited research on South African youths aging out of residential care, and there is no established protocol to guide social workers in preparing them for independent living. This study aimed to investigate what elements should be included in a protocol for social workers to effectively prepare youths leaving child and youth care centres (CYCCs). A qualitative research method has been used to achieve the aim of this study. Purposive sampling was employed to select seven CYCCs located in Gauteng province, consisting 24 social workers from the West Rand, Sedibeng and Johannesburg District Municipality. Data were collected through semi-structured, individual interviews using a prepared interview guide. The findings of this study highlight the need for the implementation of mandated preparatory protocols, encompassing life skills and healthy living, entrepreneurship skills, computer skills, interpersonal skills, how to integrate within a family, and the availability of after-care services. The study concludes that it is imperative to implement a standardised transition protocol to assist young people who are transitioning out of care. The findings of this study contribute to social work practice and policy development with evidence-based recommendations which can inform national guidelines and enhance service delivery to care leavers.